2017
DOI: 10.1159/000455144
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Vasculogenic Mimicry Formation in Gastric Carcinoma

Abstract: Background: The purpose of this study was to evaluate the clinical significance and prognostic roles of vasculogenic mimicry (VM) and elucidate their intrinsic association with molecular markers. Methods: 89 human gastric cancer cases with detailed follow-up and clinicopathologic data were collected. CD34/periodic acid-Schiff double staining was performed to validate the existence of VM. Immunohistochemistry was performed to explore the expression of different molecular factors. Results: VM was observed in 24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 27 publications
1
15
0
2
Order By: Relevance
“…To elucidate the mechanisms involved in the reverse effect of melittin on hypoxia-induced VM formation, we first examined the levels of HIF-1 α after melittin treatment. As shown in Figure 2(b), CoCl 2 treatment increased the level of HIF-1 α and its downstream target genes VEGF and MMP-9 that are involved in VM formation and tumor invasion [21]. Melittin suppressed CoCl 2 -induced upregulation of HIF-1 α , VEGF, and MMP-2/9 (Figure 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the mechanisms involved in the reverse effect of melittin on hypoxia-induced VM formation, we first examined the levels of HIF-1 α after melittin treatment. As shown in Figure 2(b), CoCl 2 treatment increased the level of HIF-1 α and its downstream target genes VEGF and MMP-9 that are involved in VM formation and tumor invasion [21]. Melittin suppressed CoCl 2 -induced upregulation of HIF-1 α , VEGF, and MMP-2/9 (Figure 2(b)).…”
Section: Resultsmentioning
confidence: 99%
“…Ever since the first description of vascular mimicry (VM) in uveal melanoma 2 as a novel paradigm for tumor perfusion, VM has been observed in various types of malignancies 6,7,14 including gastric cancer 9 . In the previous studies, conducted for VM evaluation in gastric cancer specimens, VM was recognized as consisting of periodic acid-Schiff (PAS)-positive and CD31- or CD34-negative vessels, in contrast to classic endothelial blood vessels that are double positive for both PAS and CD31 or CD34 9,25,26 . PAS was shown to stain basement membranes 25,27 and cytoplasm 9,26 of gastric tumor cells lining the external wall of the VM channels without any involvement of CD31/CD34-positive vascular endothelial cells, like the golden standard for VM in solid tumors such as melanoma 2 , breast cancer 8 , and hepatocellular carcinoma 7 .…”
Section: Discussionmentioning
confidence: 99%
“…In the previous studies, conducted for VM evaluation in gastric cancer specimens, VM was recognized as consisting of periodic acid-Schiff (PAS)-positive and CD31- or CD34-negative vessels, in contrast to classic endothelial blood vessels that are double positive for both PAS and CD31 or CD34 9,25,26 . PAS was shown to stain basement membranes 25,27 and cytoplasm 9,26 of gastric tumor cells lining the external wall of the VM channels without any involvement of CD31/CD34-positive vascular endothelial cells, like the golden standard for VM in solid tumors such as melanoma 2 , breast cancer 8 , and hepatocellular carcinoma 7 . In this study, PAS reaction was observed on the luminal surface and cytoplasm of the gastric tumor cells forming the VM channels.…”
Section: Discussionmentioning
confidence: 99%
“…Similar differences were observed in orbital rhabdomyosarcoma and adrenocorticoid carcinomas (32, 33). Gastric cancer patients with PAS+ structures were prone to present higher histological grade, metastasis, distant recurrence, and 12 months less cumulative OS (34). Similarly, VM+ prostate cancer patients correlated with Gleason score, preoperative prostate-specific antigen (PSA) levels, pathological stage and both lymph node and distant metastasis.…”
Section: Why Should We Care About Vm?mentioning
confidence: 99%